A Baker's Dozen of Top Antimicrobial Stewardship Intervention Publications for Hospitalized Patients in 2021. (4th November 2022) - Marx, Ashley H; Cluck, David; Green, Sarah B; Anderson, Daniel T; Stover, Kayla R; Chastain, Daniel B; Covington, Elizabeth W; Jones, Bruce M; Lantz, Evan; Rausch, Ethan; Tu, Patrick J Y; Wagner, Jamie L; et al.
Abstract: Keeping abreast of the antimicrobial stewardship–related articles published each year is challenging. The Southeastern Research Group Endeavor (SERGE-45) identified antimicrobial stewardship–related, peer-reviewed literature that detailed an "actionable" intervention among hospitalized populations during 2021. The top 13 publications were selected using a modified Delphi technique. These manuscripts were reviewed to highlight "actionable" interventions used by antimicrobial stewardship programs in hospitalized populations to capture potentially effective strategies for local implementation.